Factors affecting chiropractor requests for full‐length spinal radiography: A scoping review - Thomas R. Readford; Melanie Hayes; Warren Michael Reed (Journal of Medical Radiation Sciences, 2022)
Abstract Chiropractors often refer their patients for full‐length (three‐ to four‐region) radiographs of the spine as part of their clinical assessment, which are frequently completed by radiographers in medical imaging practices. Overuse of spinal radiography by chiropractors has previously been reported and remains a contentious issue. The purpose of this scoping review was to explore the issues surrounding the utilisation of full‐length spinal radiography by chiropractors and examine the alignment of this practice with current evidence. A search of four databases (AMED, EMBASE, MedLine and Scopus) and a hand search of Google was conducted using keywords. Articles were screened against an inclusion/exclusion criterion for relevance. Themes and findings were extracted from eligible articles, and evidence was synthesised using a narrative approach. In total, 25 articles were identified, five major themes were extracted, and subsequent conclusions drawn by authors were charted to identify confluent findings. This review identified a paucity of literature addressing this issue and an underrepresentation of relevant perspectives from radiographers. Several issues surrounding the use of full‐length spinal radiography by chiropractors were identified and examined, including barriers to the adherence of published guidelines for spinal imaging, an absence of a reporting mechanism for the utilisation of spinal radiography in chiropractic and the existence of a spectrum of beliefs amongst chiropractors about the clinical utility and limitations of full‐length spinal radiography. Further investigation is required to further understand the scope of this issue and its impacts for radiation protection and patient safety.